Attitudes of deaf individuals towards genetic testing of genes known to cause hearing loss. (June 2023) - Mascia, Katherine L; Robin, Nathaniel H
Congenital deafness is one of the most common birth defects reported. Approximately 70% of congenital deafness is non-syndromic, and approximately 80% of non-syndromic hearing loss results from a genetic cause. Middleton et al .'s1998 study highlighted the negative attitudes of culturally Deaf individuals towards genetic testing for genes known to cause hearing loss. While studies concerning genetic testing for deafness genes reference Middleton's study, to our knowledge a re-evaluation of the attitudes of Deaf individuals towards genetic testing has not been conducted recently. The purpose of this study is to re-establish attitudes of Deaf individuals towards genetic testing of genes known to cause hearing loss. A computer-based questionnaire was distributed to members of the Deaf community. Responses of participants were recorded and analyzed. The primary investigator then attended Deaf community events and the 2015 Alabama Association of the Deaf Conference, and recruited individuals interested in participating in the study. The surveys were distributed to these individuals and their anonymous responses were analyzed. Our results show there are more positive attitudes within the Deaf community towards genetic counseling, genetic testing, and prenatal testing of genes known to cause hearing loss than were previously documented, although negative attitudes are still present. Additionally, our study shows there is a desire among members of the Deaf community to learn more about and potentially receive these services, despite the fact they are rarely offered by healthcare providers.